INTENSIFICATION OF PEOPLE’S SUGARCANE PROGRAM IN JEMBER REGENCY 1975-1998 - Ifana, Novelia Putri Ika; Akhmad Ryan Pratama; Robit Nurul Jamil; Mohamad Na’im; Gusti Ngurah Ary Kesuma Puja; Kayan Swastika (History Education, University of Jember, 2025)
The People's Sugarcane Intensification Program (TRI) is a policy issued by the New Order Government through Presidential Instruction Number 9 of 1975 which aims to increase the productivity and income of sugarcane farmers. This research aims to examine the implementation of the People's Sugar Cane Intensification (TRI) Program in Jember Regency in 1975-1998. This research method uses historical methods, with source collection techniques through literature studies and interviews. The results of the study indicate that Jember Regency meets the criteria to be a target area for TRI because it has suitable geographical and social conditions. The implementation of the TRI program in Jember Regency is in accordance with the Decree of the Minister of Agriculture/Chairman of the Bimas Supervisory Agency No. 011/SK/MENTAN/BPB/3/1976. The impacts of the TRI program are on the social sector such as increasing farmer solidarity, and the impact on the economic sector such as increasing farmer income and the amount of sugar cane production throughout the Jember region.